2017
DOI: 10.1093/mnras/stx1896
|View full text |Cite
|
Sign up to set email alerts
|

Witnessing galaxy assembly in an extended z≈3 structure

Abstract: We present new observations acquired with the Multi Unit Spectroscopic Explorer instrument on the Very Large Telescope in a quasar field that hosts a high columndensity damped Lyα absorber (DLA) at z ≈ 3.25. We detect Lyα emission from a nebula at the redshift of the DLA with line luminosity (27 ± 1) × 10 41 erg s −1 , which extends over 37±1 kpc above a surface brightness limit of 6×10 −19 erg s −1 cm −2 arcsec −2 at a projected distance of 30.5±0.5 kpc from the quasar sightline. Two clumps lie inside this ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 104 publications
(131 reference statements)
2
72
0
Order By: Relevance
“…Table 1 indicates the ions used to estimate the metallicity of the DLAs in the sample. Fumagalli et al (2017b) showed that in the case of J0255+0048 the Si II column density estimated with Voigt profile decomposition of HIRES and X-Shooter data was consistent with the value obtained with ESI and the apparent optical depth method. We therefore conclude the ionic column densities to be robust and do not re-estimate them.…”
Section: Metallicitiessupporting
confidence: 82%
See 1 more Smart Citation
“…Table 1 indicates the ions used to estimate the metallicity of the DLAs in the sample. Fumagalli et al (2017b) showed that in the case of J0255+0048 the Si II column density estimated with Voigt profile decomposition of HIRES and X-Shooter data was consistent with the value obtained with ESI and the apparent optical depth method. We therefore conclude the ionic column densities to be robust and do not re-estimate them.…”
Section: Metallicitiessupporting
confidence: 82%
“…Notably, DLA J1220+0921 in our sample is very metal-poor, sitting at Z/Z = −2.33 although still somewhat above the metallicity floor at Z/Z −3 (Prochaska et al 2003;Rafelski et al 2012). One sightline in our sample was previously presented in Fumagalli et al 2017b, the DLA was revealed to be part of a 50 kpc structure which may be evidence of an ongoing merger.…”
Section: Sample Selectionmentioning
confidence: 77%
“…In particular, thanks to its large 1 arcmin 2 field of view, its extended wavelength coverage in the optical, and its exquisite sensitivity, MUSE has become the ideal instrument for studies of the CGM of galaxies in quasar fields (e.g. Schroetter et al 2016;Fumagalli et al 2016Fumagalli et al , 2017bPéroux et al 2017;Bielby et al 2017;Klitsch et al 2018;Chen et al 2019).…”
mentioning
confidence: 99%
“…As in previous analyses of MUSE data (e.g. Fumagalli et al 2017b;Mackenzie et al 2019;Lofthouse et al 2019;Fossati et al 2019), we conduct a redshift survey of galaxies detected in the continuum together with a search for line emitters in the cube. 18 19 20 21 22 23 24 25 26 27 28 29 30 31 33 34 36 37 38 39 41 42 43 44 45 46 47 48 49 50 52 53 54 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 80 81 82 84 86 87 89 90 91 92 93 95 96 97 98 99 100 101 103 104 105 106 107 108 110 111 112113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 129 130 131 132 133 ...…”
Section: Search For Associated Galaxiesmentioning
confidence: 99%
“…Observations have been reduced following the methodology described in previous work (Fumagalli et al 2016b(Fumagalli et al , 2017bLofthouse et al 2019). Briefly, we first use the standard ESO pipeline (v2.4.1; Weilbacher et al 2014) to perform basic reduction by applying calibrations.…”
mentioning
confidence: 99%